MORAL HARASSMENT IN THE MILITARY POLICE OF TOCANTINS: AN ANALYSIS OF THE REGULATORY GAP AND ORGANIZATIONAL IMPACTS (Editora Impacto Científico, 2025)
This article discusses moral harassment within the Military Police of the State of Tocantins (PMTO), emphasizing the regulatory gap and the organizational impacts resulting from the absence of internal regulations on the subject. The general objective of the research is to analyze how the lack of regulation and awareness policies regarding moral harassment in the PMTO affects the mental health, organizational culture, and professional performance of service members. This is a qualitative, descriptive, and documentary study based on classical and contemporary works in organizational psychology and human resource management, as well as institutional and legal documents such as the Superior Military Court Resolution No. 333/2023 and Bill No. 4,752/2024. The findings reveal that the absence of specific guidelines weakens the protection of military personnel and undermines the organizational climate. It was also found that institutional omission contributes to organizational silence and the normalization of abusive practices. The study proposes educational and preventive guidelines focused on ethical training, the strengthening of humanized leadership, and the creation of support channels. In conclusion, the general objective was achieved.DOI: https://doi.org/10.56238/edimpacto2025.090-047